The Dead Sea scrolls : a biography - Collins, John J. (John Joseph), 1946- (Lives of great religious books., 2012)
Since they were first discovered in the caves at Qumran in 1947, the Dead Sea Scrolls have aroused more fascination--and more controversy--than perhaps any other archaeological find. They appear to have been hidden in the Judean desert by the Essenes, a Jewish sect that existed around the time of Jesus, and they continue to inspire veneration and conspiracy theories to this day. John Collins tells the story of the bitter conflicts that have swirled around the scrolls since their startling discovery, and sheds light on their true significance for Jewish and Christian history. Collins.